Assessment of the hydro-thermal performance for a novel hexagonal mini-channel heat sink for cooling a cylindrical heat source - Mustafa Awaad Khalifa; Hayder Mohammad Jaffal (International Journal of Thermofluids, 2024)
Liquid cooling using a mini-channel heat sink (MHS) has been highly efficient in cooling rectangular and cylindrical lithium batteries. This work proposed a new hexagonal MHS (HMHS) to cool a cylindrical heat source instead of the traditional cylindrical with smooth MHS (CSMHS). In addition to the smooth channels, four obstructed channels were proposed to further enhance the thermal performance of this HMHS. The obstructions used include: semicircular ribs–cavities, semicircular ribs–secondary flow, semicircular pin fins and semicircular pin fins–cavities. This study was numerically conducted using the finite volume method under water Reynolds number ranging from 100 to 800. CSMHS and HMHS with semicircular pin fins were manufactured and tested to verify the validity of the numerical results. Results showed that the HMHS exhibited superior hydro-thermal performance compared with the CSMHS. In addition, the HMHS with obstructed channels contributes to a significant improvement in thermal performance. The percentages of Nusselt number improvement with all channels were approximately: 12.3%, 60.5%, 71.5%, 104% and 112% for smooth, semicircular ribs–cavities, semicircular rib–secondary flow, semicircular pin fins and semicircular pin fins–cavities, respectively. Amongst all the channels, the channels with semicircular pin fins achieved the best performance with a hydro-thermal performance factor of 1.67.